2021
DOI: 10.1038/s41598-020-77905-2
|View full text |Cite
|
Sign up to set email alerts
|

Solanum linnaeanum and Solanum sisymbriifolium as a sustainable strategy for the management of Meloidogyne chitwoodi

Abstract: Root-knot nematodes (RKN), Meloidogyne spp., are important crop pests that cause severe losses in crop production worldwide, reducing both productivity and crop quality. Meloidogyne chitwoodi Golden, O'Bannon, Santo & Finley, 1980 is considered a quarantine organism by the European and Mediterranean Plant Protection Organization (EPPO) causing damage in tomato and potato crops. The development of nonchemical and sustainable management strategies to reduce nematode damage is crucial. The resistance of Solan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Among these, S. linnaeanum did not allow M. chitwoodi to form females and yielded 100% males however very few females were noted in S. sisymbriifolium roots. This study suggested that S. linnaeanum can be used as a new source of resistance against M. chitwoodi 148 . However, the establishment of these crops under field conditions needs to be evaluated before their inclusion in an integrated nematode management programme against nematodes infecting potatoes.…”
Section: Trap Croppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, S. linnaeanum did not allow M. chitwoodi to form females and yielded 100% males however very few females were noted in S. sisymbriifolium roots. This study suggested that S. linnaeanum can be used as a new source of resistance against M. chitwoodi 148 . However, the establishment of these crops under field conditions needs to be evaluated before their inclusion in an integrated nematode management programme against nematodes infecting potatoes.…”
Section: Trap Croppingmentioning
confidence: 99%
“…This study suggested that S. linnaeanum can be used as a new source of resistance against M. chitwoodi. 148 However, the establishment of these crops under field conditions needs to be evaluated before their inclusion in an integrated nematode management programme against nematodes infecting potatoes. Additionally, the host status of S. linnaeanum against PCN needs further investigation.…”
Section: Efficacy Against Pcnmentioning
confidence: 99%
“…Many wild Solanum species display resistance to Meloidogyne spp. [ [26] , [27] , [28] , [29] ]. Solanum sisymbriifolium , originating from South America, with effects on several PPN species, and S. linnaeanum , native to South Africa and present in the South of Portugal, are two wild Solanum species [ [29] , [30] , [31] , [32] , [33] , [34] , [35] ].…”
Section: Introductionmentioning
confidence: 99%
“…These types of RKN, including Meloidogyne javanica , are economically important PPN. They are responsible for significant crop yield losses, in particular with tomato plants, which are among the major vegetable crops grown and consumed worldwide (Perpétuo et al, 2021 ). In terms of controlling PPN crop infections including from RKN, currently, there are many sustainable practices and strategies employed including crop rotation, growing resistant varieties (Palomares‐Rius et al, 2021 ), and biological control (Pulavarty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%